The action of Palbociclib on the Cell Cycle of Head and Neck Squamous Cell Carcinoma: A Systematic Review - Teixeira, Maria Eduarda Bertolazzi; Silva, João Pedro Fabrini da; Herrera, Ana Cristina da Silva do Amaral (Brazilian Journal of Oncology, 2025)
This study evaluates the action of Palbociclib in the cell cycle of HPV-negative head and neck squamous cell carcinoma. Initially approved for HER2- and HR + breast cancer. Palbociclib induces cellular senescence, increases the efficacy of Cetuximab, restores p16 function and decreases phosphorylated Rb, suggesting an improvement in survival in both cancers.
Keywords: cyclin-dependent kinase inhibitor proteins; tumor agnostic therapy; squamous cell carcinoma of head and neck; palbociclib; medical oncology